ENHANCING LANGUAGE PROFICIENCY THROUGH THE INTEGRATION OF SPEAKING, LISTENING, READING, AND WRITING SKILLS IN EFL CONTEXTS (Eureka Journal of Language, Culture & Social Change, 2026)
In the era of communicative language teaching, the compartmentalization of language skills (reading, writing, listening, and speaking) is increasingly viewed as an artificial barrier to natural language acquisition. This article explores the theoretical foundations and practical implications of the Integrated Skills Approach (ISA). By analyzing current pedagogical frameworks, the study argues that integrating these four skills mirrors real-world communication and leads to higher learner engagement and cognitive development. The paper provides actionable strategies for educators to synchronize receptive and productive skills in English as a Foreign Language (EFL) classroom.
Keywords: Integrated Skills Approach, EFL, Language Acquisition, Communicative Competence, Pedagogy.